Introduction to Electronic Commerce and Social Commerce - Turban, Efraim; Whiteside, Judy; King, David; Outland, Jonathan (Springer International Publishing, 2017)
This is a complete update of the best-selling undergraduate textbook on Electronic Commerce (EC). New to this 4th Edition is the addition of material on Social Commerce (two chapters); a new tutorial on the major EC support technologies, including cloud computing, RFID, and EDI; ten new learning outcomes; and video exercises added to most chapters. Wherever appropriate, material on Social Commerce has been added to existing chapters. Supplementary material includes an Instructor's Manual; Test Bank questions for each chapter; Powerpoint Lecture Notes; and a Companion Website that includes EC support technologies as well as online files. The book is organized into 12 chapters grouped into 6 parts. Part 1 is an Introduction to E-Commerce and E-Marketplaces. Part 2 focuses on EC Applications, while Part 3 looks at Emerging EC Platforms, with two new chapters on Social Commerce and Enterprise Social Networks. Part 4 examines EC Support Services, and Part 5 looks at E-Commerce Strategy and Implementation. Part 6 is a collection of online tutorials on Launching Online Businesses and EC Projects, with tutorials focusing on e-CRM; EC Technology; Business Intelligence, including Data-, Text-, and Web Mining; E-Collaboration; and Competition in Cyberspace.
Keywords: Business.; Management information systems.; Electronic commerce.; elektronické knihy; electronic books